Ethical issues related to computerised family medical histories in sickle cell disease: Inforare - Franrenet, Sandra (Journal of medical ethics, 2010)
The Inforare project aims to set up a system for the sharing of clinical and familial data, in order to study how genes are related to the severity of sickle cell disease. While the computerisation of clinical records represents a valuable research goal, an ethical framework is necessary to guarantee patients' protection and their rights in this developing field. Issues relating to patient information during the Inforare study were analysed by the steering committee. Several major concerns were discussed by the committee and formalised in the patients' information letter: educating patients to aid the recruitment of family members, rules of confidentiality and the disclosure of aggregate, individual and unexpected research results. This paper presents the main issues addressed.